(3GdehLR aj GdWQb GdEMUGFjIs - (3eMeO UHMj(B, (3CHh UGdMs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2002)
(3LeY GdHjGfGJ hYQVgG(B-(3ebGjjS GdfRYI GdeQcRjI(B-(3ebGjjS GdJTJJ(B-(3GdYRhe hGdJaQWM hGdEdJhGA(B-(3GdEMJeGdGJ(B-(3GdJhRjY GdWHjYj(B-(3GdEQJHGW hGdEfMOGQ(B-(3GdSdGSd GdRefjI(B-(3GdCQbGe GdbjGSjI(B-(3GdJbOjQ hGNJjGQ GdaQVjGJ(B-(3GdEMUGAGJ GdMjhjIs
Keywords: (3GdEMJeGdGJs; (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdGMUGAGJ GdMjhjIs